The trial of Dr. Spock : the Rev. William Sloane Coffin, Jr., Michael Ferber, Mitchell Goodman, and Marcus Raskin - Mitford, Jessica, 1917-1996. (London : Macdonald, 1969)
Chronicle of events in Boston, 1968 surrounding their prosecution on charges of conspiracy to counsel, aid and abet violations of the Selective Service Act.
Appendices'(p. [249]-272):--1. The indictment.--2. Overt act'1,'A call to resist illegitimate authority.'--3. Overt act'3, Michael Ferber's speech,'A time to say no.'--4. Overt act'4, Speech in Boston by the Rev. William Sloane Coffin, Jr.--5. Overt act'6, Statement before the Department of Justice by the Rev. William Sloane Coffin, Jr.--6. The role of the American Civil Liberties Union in the case of the Boston Five.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Trials (Conspiracy) -- United States; Spock, Benjamin, -- 1903-1998.